Peningkatan Sumber Daya Manusia Dalam Rangka Pengembangan Pengelolaan BUM Desa di Kelurahan Kalirejo Ungaran Timur - Retno Anggoro; Widanto Mukti Adi; Lia Retian Asfirah; Fajar Sari Kurniawan; Fitri Suprapti (JEPEmas: Jurnal Pengabdian Masyarakat (Bidang Ekonomi), 2023)
In economic development and community welfare at the village level, the role of Village Owned Enterprises (BUM) Desa is becoming increasingly important. BUM Desa is an economic institution managed by local communities with the aim of improving local resource management, creating jobs, and improving economic and social conditions in village areas. In order to achieve this goal, one of the key factors that must be considered is the increase in human resources involved in the management of BUM Desa. in order to explore a more in-depth understanding of the importance of increasing human resources in the context of developing the management of BUM Desa in the Kalirejo Village, Ungaran Timur. This activity is expected to provide valuable insights for readers regarding the challenges and opportunities in the development of BUM Desa as well as effective strategies for increasing the human resources involved in its management.